URGENSI BAHASA ARAB DALAM MENGATASI TERJADINYA BIAS GENDER (Penafsiran Teks dan Konteks Bahasa dalam Wacana Keagamaan) - Muhammadun, Muzdalifah (AL-MAIYYAH, 2015)
Arabic language is considered a tool of communication playing an exceedingly role in uttering divine messages. Nonetheless, this language must be analyzed properly so that some verses that seem containing gender bias as the result of characters and symbols in this language can be avoided. In this way, discrimination to women on behalf of religious (Islamic) teaching will not occur. The point is that even though messages of the QurâÄn are universal and permanent, the verbalization of the messages is closely related to the situation of the Arabic community at the time QurâÄn was revealed. Therefore, we must carefully study in identifying these two dimensions of the messages.